The global financial resource curse - Gianluca Benigno; Luca Fornaro; Martin Wolf (Federal Reserve Bank of New York, 2020)
Since the late 1990s, the United States has received large capital flows from developing countries and experienced a productivity growth slowdown. Motivated by these facts, we provide a model connecting international financial integration and global productivity growth. The key feature is that the tradable sector is the engine of growth of the economy. Capital flows from developing countries to the United States boost demand for U.S. non-tradable goods. This induces a reallocation of U.S. economic activity from the tradable sector to the non-tradable one. In turn, lower profits in the tradable sector lead firms to cut back investment in innovation. Since innovation in the United States determines the evolution of the world technological frontier, the result is a drop in global productivity growth. We dub this effect the global financial resource curse. The model thus offers a new perspective on the consequences of financial globalization, and on the appropriate policy interventions to manage it.
Keywords: E44; F21; F43; F62; O24; O31; 330; global productivity growth; international financial integration; capital flows; U.S.productivity growth slowdown; low global interest rates; Bretton Woods II; export-led growth